Sex in peace operations / Gabrielle Simm. - Simm, Gabrielle (Cambridge University Press, 2013)
Gabrielle Simm's critical re-evaluation of sex between international personnel and local people examines the zero tolerance policy on sexual exploitation and abuse and its international legal framework. Whereas most preceding studies of the issue have focused exclusively on military peacekeepers, Sex in Peace Operations also covers the private military contractors and humanitarian NGO workers who play increasingly important roles in peace operations. Informed by socio-legal studies, Simm uses three case studies (Bosnia, West Africa and the Democratic Republic of the Congo) to illustrate the extent of the problem and demonstrate that the problems of impunity for sexual crimes are not just a failure of political will but the result of the structural weaknesses of international law in addressing non-state actors. Combining the insights of feminist critique with a regulatory approach to international law, her conclusions will interest scholars of international law, peace and conflict studies, gender and sexuality, and development.